2008
DOI: 10.1016/j.jcis.2007.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Calcium–phosphorus interactions at a nano-structured silicate surface

Abstract: Nano-structured calcium silicate (NCS), a highly porous material synthesized by controlled precipitation from geothermal fluids or sodium silicate solution, was developed as filler for use in paper manufacture. NCS has been shown to chemisorb orthophosphate from an aqueous solution probably obeying a Freundlich isotherm with high selectivity compared to other common environmental anions. Microanalysis of the products of chemisorption indicated there was significant change from the porous and nano-structured mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…The activation energy for this ageing step process been reported as between 95-105 kJ mol À1 . 10,11 It has also been shown by Lai that reinforced NCSH material exhibits similar adsorption characteristics to those observed by Southam. It was found that the material possessed a maximum sorption capacity for phosphate of 1.94 mmol P per g NCSH.…”
Section: Phosphate Sorptionmentioning
confidence: 52%
See 1 more Smart Citation
“…The activation energy for this ageing step process been reported as between 95-105 kJ mol À1 . 10,11 It has also been shown by Lai that reinforced NCSH material exhibits similar adsorption characteristics to those observed by Southam. It was found that the material possessed a maximum sorption capacity for phosphate of 1.94 mmol P per g NCSH.…”
Section: Phosphate Sorptionmentioning
confidence: 52%
“…Of the various calcium phosphates, the apatites have the lowest solubility; pK-values for hydroxyapatite, Ca 5 (PO 4 ) 3 (OH), range from 54.4 to 58.5 at 25 C. 18 Despite the low solubility of the apatites, calcium and phosphate are readily found in solution at concentrations far exceeding that for the precipitation of apatite phases, due to the large activation energy of the precipitation step. 19,20 Phosphate sorption by nano-structured calcium silicate hydrate Southam, in 2004Southam, in , 9 2005 10 and 2008 11 conducted extensive studies of the characteristics of nano-structured calcium silicate hydrate (NCSH) with regard to its sorption of phosphate. 19 The phosphate ion, PO 4 3À is not encountered in this initial precipitate, which subsequently ages to form the apatite phase over a period of several hours.…”
Section: Phosphate Sorptionmentioning
confidence: 99%
“…19,21) Synthetic CSH compounds has recently been examined in phosphorus recovery from wastewater as crystal seeds, since Ca 2 + and OH − ions released from CSH react with phosphate species to produce HAP crystals on the surface. 22,23) Since the slag-made CSH has a higher specific surface area and unique composition, it is expected to show a superior performances for phosphorus adsorption compared with pure synthetic analogue previously reported. Furthermore, application of the slag-made CSH as an alternative low-cost adsorbent for phosphorus would not only lead to a cost-effective phosphorus removal and recovery process, but also contribute to the sustainable management of BF slags produced in iron-making industry.…”
Section: )mentioning
confidence: 99%
“…These combined analyses conclusively suggest that the phosphate ions are fixed onto the adsorbent surface in the form of amorphous calcium phosphate species, where the surface exposed Ca 2 + sites and Ca 2 + ions eluted into aqueous solution are the main active species. 22,23) …”
Section: Study Of Adsorption Mechanismmentioning
confidence: 99%
“…This is because the original dense pore structure can be blocked by HAP crystallization quickly at the beginning of reaction stage. The dense pore structure and poor solubility of CSH are therefore the two key factors of phosphate recovery [24]. …”
Section: Introductionmentioning
confidence: 99%